Captive prince - Pacat, C. S. (Pacat, C. S. Captive prince trilogy ;, 2015)
When beloved warrior hero Damen's brother siezes the throne of Akielos unjustly, rightful heir Damen is sold as a pleasure slave to Prince Laurent of the enemy Vere Kingdom, and is soon caught up in court intrigue that threatens him and his new master.